Pengaruh E-Commerce Shopee dan Kreativitas Mahasiswa terhadap Minat Berwirausaha Online Mahasiswa Jurusan Administrasi Niaga Politeknik Negeri Ujung Pandang - Dalif, Nurul Athifah; Usman, Ahmadi; Sari, Syahriah (Journal of Business Administration (JBA), 2024)
This research is aimed find out students' perceptions of the students' creativity that must be possessed in online entrepreneurship, find out students' perceptions of online entrepreneurial intention, find out the effect of shopee e-commerce toward students' online entrepreneurial intention partially, find out the effect of students’ creativity toward students' online entrepreneurial intention partially, find out the effect of shopee e-commerce and students’ creativity toward students' online entrepreneurial intention simultaneously. The population of this research were students of the Department of Business Administration, the State Polytechnic of Ujung Pandang who had completed entrepreneurship course and used shopee   e-commerce with total of 399 students. In this research, the sampling technique used was purposive sampling and the calculation based of the slovin’s formula, which resulted 200 students as sample. This research data was obtained from distributing online questionnaires. The data gathered obtained is then processed and analyzed by using SPSS Statistics version 25 by conducting validity and reliability tests, descriptive statistical analysis, classical assumption tests, multiple linear regression tests, and hypothesis tests. The results of this research showed that: 1) students' perceptions of shopee e-commerce in online entrepreneurship is in the good category; 2) students' perceptions of the students' creativity that must be possessed in online entrepreneurship is in the high category; 3) students' perceptions of online entrepreneurial intention is in the high category; 4) shopee e-commerce partially had an effect on online entrepreneurial intention; 5) student creativity had no effect on online entrepreneurial intention; 6) shopee e-commerce and student creativity simultaneously had an effect on online entrepreneurial intention.